Association of anaesthesia type with one-year mortality after surgery in elderly patients: a secondary retrospective cohort study - Ping Jin; Fengjiao Lu; Rongzhi Zhang; Panpan Lü; Shixiong Gao (BMC Anesthesiology)
Abstract Objective To examine whether regional anaesthesia (RA) versus general anaesthesia (GA) is associated with the one-year postoperative mortality among the older surgical patients. Methods We conducted a single-center retrospective cohort study from 2012 to 2016. Patients aged 70 years or older who underwent surgery were included, and those who underwent transplantation, burn surgery, or minor procedures were excluded. The primary exposure was anaesthesia type (RA vs. GA); the main outcome was one-year all-cause mortality, which was verified through hospital records and a national registry. Demographic, clinical, and laboratory variables were included as covariates. Multivariable-adjusted logistic regression models were used to evaluate the independent effect of anaesthesia methods on one-year mortality. Kaplan-Meier curves assessed survival rates by anaesthesia method, with log-rank tests comparing the curves. Main results Among 16,599 older adults, 29.7% received RA. The one-year mortality rate was lower in the RA group (6.44%) than in the GA group (9.52%), yielding an adjusted odds ratio of 0.72 (95% CI, 0.63–0.82). K‒M analyses revealed improved survival in the RA group (log-rank P < 0.05). Propensity score matching and inverse probability weighting analyses corroborated these findings. The E-value of 2.12 demonstrates the robustness of the results against unmeasured confounding. Conclusions Regional anaesthesia may be linked to better one-year survival in older patients. Although other confounding factors cannot be excluded, these findings underscore the need for multicenter, prospective investigations to inform perioperative decisions in geriatric populations.